PENGARUH FAKTOR PENDIDIKAN, PENGALAMAN KERJA, DAN PELATIHAN TERHADAP PENGETAHUAN APARATUR PAJAK TENTANG TAX AVOIDANCE ( Studi Kasus atas Aparatur Pajak pada KPP Pratama Batu) - Noorina Ayuningtyas; M. Khoiru Rusydi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to know the influence of education, work experience, and training on tax employee’s knowledge about tax avoidance. This research is using the primary data from questionnaire. This research is using survey method and regression analysis testing. Sample of this research is 67 from KPP Pratama Batu’s tax employees. Independent variables for this research are education, work experience, and training. Whereas the dependent variable is tax employee’s knowledge about tax avoidance. The first step on the research is testing a reliability and validity of each variable. And then the second step is regression testing of three variables on tax employee’s knowledge about tax avoidance. Simultaneous results is showing that three variables have a significant in amount of 0,000. Partial results shows that education have a 0,000 signification; work experience is 0,049; and training is 0,049. The conclusion of this research are education, work experience, and training have an influence on tax employee’s knowledge about tax avoidance. Keywords : education, work experience, training, tax employee, knowledge, and tax avoidance